Comparative study on the effect of rhombus and rectangular openings of shear wall on the behavior of tall buildings - Syamsir A.; Malekzadah A.R.; Naganathan S.; Itam Z.; Nor N.M.; Chairi M.; Imani R. (American Institute of Physics Inc., 2024)
Reinforced concrete shear wall systems are a standout amongst the most commonly utilized horizontal load opposing systems in tall structure. It is important to determine efficient, effective shape of opening of shear wall in tall building. This paper investigates the effect of rhombus and rectangular opening on lateral displacement, base shear and stress of shear wall of tall building. A residential tall building of (12 Story) having base size of 20m 10m with height of floor of 3m is considered. In this paper 12% opening area of concentric rhombus dan rectangular opening of shear wall were modelled. It was found that rhombus produce lower lateral displacement, base shear and stress which is good for tall building. 2023 Author(s).